METTL1-mediated m7G tRNA modification drives papillary thyroid cancer progression and metastasis by regulating the codon-specific translation of TNF-α - Weiwei Li; Ruiwang Xie; Huaying Chen; Junyu Lin; Minjie Zhong; Junsi Zhang; Shengkai Zheng; Cen Jiang; Xiangjin Chen; Sunwang Xu (Cell Death and Disease)
Abstract N7-methylguanosine (m7G) modification of transfer RNA (tRNA) is essential for the biological functions of tRNAs and has been found to play a regulatory role in a variety of human cancers. However, the biological function of METTL1-mediated m7G tRNA modification in papillary thyroid cancer (PTC) is unclear. Here, we found that METTL1 is significantly upregulated in PTC tissues compared to normal control tissues and is associated with poor PTC prognosis. Functional analysis confirmed that METTL1 promotes the proliferation and metastasis of PTC cells in a manner dependent on its tRNA methyltransferase activity. Mechanistically, METTL1 knockdown leads to a decrease in the abundance of certain m7G-modified tRNAs, which suppresses the m7G tRNA modification-mediated codon-specific translation of TNF-α. Furthermore, exogenous supplementation with TNF-α partially reversed the decrease in the proliferation and metastasis of PTC cells induced by METTL1 deletion. Positive correlations between METTL1, WDR4, and TNF-α expression, which affect the proliferation and metastasis of PTC, were confirmed via analysis of microarrays containing PTC tissues. These results demonstrate the oncogenic role of METTL1-mediated m7G tRNA modification in regulating codon-specific translation efficiency in PTC and suggest that targeting METTL1 may be a promising therapeutic approach for overcoming PTC progression by inhibiting PTC cell proliferation and metastasis.